1,
Đặt \(A=\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(\left(2-1\right)A=\left(2-1\right)\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(1A=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(A=\left(2^4-1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(A=\left(2^8-1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(A=\left(2^{16}-1\right)\left(2^{16}+1\right)\)
\(A=2^{32}-1\)
Vậy \(A=2^{32}-1\)
2, \(x^2-6x=-9\)
\(x^2-6x+9=0\)
\(\left(x-3\right)^2=0\)
\(x-3=0\)
\(x=3\)
Vậy \(x=3\)